2009
DOI: 10.1677/joe-09-0034
|View full text |Cite
|
Sign up to set email alerts
|

Two divergent leptin paralogues in zebrafish (Danio rerio) that originate early in teleostean evolution

Abstract: We describe duplicate leptin genes in zebrafish (Danio rerio) that share merely 24% amino acid identity with each other and only 18% with human leptin. We were also able to retrieve a second leptin gene in medaka (Oryzias latipes). The presence of duplicate leptin genes in these two distantly related teleosts suggests that duplicate leptin genes are a common feature of teleostean fishes. Despite low primary sequence conservation, we are confident in assigning orthology between mammalian and zebrafish leptins f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
167
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(179 citation statements)
references
References 39 publications
12
167
0
Order By: Relevance
“…Leptin amino acid sequence is conserved in mammalian and fish classes even though it seems to show higher diversity within teleosts (Kurokawa et al 2005). Thus recent reports identify additional leptin in several teleosts (leptin-a and leptin-b), such as carp (Cyprinus carpio), zebrafish (Danio rerio) and medaka (Oryzias latipes) (Huising et al 2006;Gorissen et al 2009;Kurokawa & Murashita 2009). Leptin-a shares high primary sequence conservation within zebrafish and carp (61%), whereas leptin-b shares only 25% amino acid identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin amino acid sequence is conserved in mammalian and fish classes even though it seems to show higher diversity within teleosts (Kurokawa et al 2005). Thus recent reports identify additional leptin in several teleosts (leptin-a and leptin-b), such as carp (Cyprinus carpio), zebrafish (Danio rerio) and medaka (Oryzias latipes) (Huising et al 2006;Gorissen et al 2009;Kurokawa & Murashita 2009). Leptin-a shares high primary sequence conservation within zebrafish and carp (61%), whereas leptin-b shares only 25% amino acid identity.…”
Section: Discussionmentioning
confidence: 99%
“…Among teleosts, the presence of leptin orthologues has been recently reported in pufferfish, medaka, carp and zebrafish, suggesting the possibility of a redundant leptin network in teleosts (Gorissen et al 2009). Leptin is a potent stimulator of pituitary prolactin release in tilapia (Tipsmark et al 2008), it regulates the reproductive system in sea bass (Peyon et al 2001), it is responsible for food intake in rainbow trout ) and in goldfish (Volkoff et al 2003), and body weight regulation in goldfish (De Pedro et al 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Leptins also were identified in non-mammalians, including birds [3][4][5], reptiles [2], amphibians [6][7][8], and teleosts, the later generally possess duplicated leptins [8][9][10][11][12][13][14][15]. Leptin has been found to be responsible for the regulation of body weight and energy homeostasis [16,17], and it also is involved in regulating appetite, reproduction [18], the immune system [19], bone formation [20], angiogenesis [21], and stress response [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although, positive selections of leptins are revealed in several mammal lineages, for example, pikas (Ochotona curzoniae), Cetacea and Pinnipedia, and heterothermic bats [24][25][26], the conserved gene structure (three exons separated by two introns) and secondary and tertiary structures of leptins were found from teleosts to mammals [2,3,6,11,27,28]. Phylogeny reconstruction of vertebrate leptins showed that most vertebrates form distinct clades with topology consistent with the generally accepted vertebrate topology except that the relationships among teleosts remain inconsistent [2,11,29].…”
Section: Introductionmentioning
confidence: 99%